1985
DOI: 10.1056/nejm198512263132601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Captopril on Heavy Proteinuria in Azotemic Diabetics

Abstract: We investigated whether captopril, an angiotensin-converting-enzyme inhibitor, would reduce proteinuria in patients with advanced diabetic nephropathy. Captopril (37.5 mg given in divided doses three times daily) was administered to 10 azotemic diabetics with heavy proteinuria. Urinary protein decreased promptly within two weeks (from 10.6 +/- 2.2 to 6.1 +/- 1.4 g per day [mean +/- S.E.M.]; P less than 0.01). The decrease in proteinuria did not coincide with a fall in systemic blood pressure or in the blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
0
6

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(128 citation statements)
references
References 8 publications
5
116
0
6
Order By: Relevance
“…Since the recognition of ACE-I as a renal protective agent, [1][2][3][4] the inhibition of ANG II activity has been anticipated to serve to prevent renal injury. Indeed, a couple of recent large-scale trials also demonstrate that ARB exerts salutary action in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the recognition of ACE-I as a renal protective agent, [1][2][3][4] the inhibition of ANG II activity has been anticipated to serve to prevent renal injury. Indeed, a couple of recent large-scale trials also demonstrate that ARB exerts salutary action in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recently, two types of pharmacological tools, ie, ANG-converting enzyme inhibitors (ACE-I) and ANG receptor antagonists (ARB), are in clinical use, and several large-scale clinical trials have demonstrated the beneficial effect of these agents on renal disease. [3][4][5][6] As expected from the haemodynamic action on blood pressure and renal arterioles, both agents reduce glomerular capillary pressure, which subsequently would exert a favourable effect on the progression of renal disease, in concert with the inhibitory action on the direct glomerular injury induced by ANG II.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that inhibition of the RAS delays the progression of diabetic nephropathy (1)(2)(3)(4). At present, two types of RAS inhibitors with different mechanisms of action are commonly used: angiotensin-converting enzyme inhibitor (ACEI), and angiotensin type 1 receptor blocker (ARB).…”
Section: Introductionmentioning
confidence: 99%
“…There has been much interest in the role of CEI in preventing progression in experimental (Zatz et al 1986) and clinical diabetic nephropathy, (Taguma et al 1985;Bjorck et al 1986;Hommel et al 1986) and this has been discussed in previous papers. Reports are now appearing which examine the role of CEI in retarding progressive loss of renal function, independent of their effects on systemic blood pressure.…”
Section: Converting Enzyme Inhibitors and The Kidneymentioning
confidence: 99%